Integration of Micro E-Learning Content in SIPEJAR Geoedupreneurship Course Based on Real Life Entrepreneurship - Wahyudi, Adip; Deffinika, Ifan; Mutia, Tuti; Maulana, Feri Fahrian; Maghfiroh, Ainun; Prista, Dynda; Indraningrum Shrestha, Maria Emerita (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
The era of digital technology development puts the burden on the learning environment to be more interactive and relevant. One of them is the Geoedupreneurship course, from the point of view of low motivation from students due to a lack of technology integration. Therefore, the researcher aims to develop micro e-learning content based on real-life entrepreneurship to increase students' engagement and understanding of some entrepreneurial issues. The research method used was Research and Development with the Dick and Carey model combined with The Successive Approximation Model, to strengthen the systematic and adaptive aspects of the process. The research subjects consisted of 30 geography students. The data collection method used was a questionnaire. Data analysis used in this development research is quantitative with descriptive statistics. The result revealed that the developed Micro E-Learning content was valid, with an 87.25% indicator from the expert validation result. During its experimental testing on students, motivation and comprehension were improved, while interactivity and access satisfaction were at stake. The inclusion shows that the SIPEJAR-based Micro E-Learning enhances the quality of Geoedupreneurship learning, provides students with better preparation for their entrepreneurial future and an engaging and relevant learning experience.